Answer:
-60x + 10
Step-by-step explanation:
-5 x 2(6x - 1)
-10 (6x - 1)
-60x + 10
Answer:
l
Step-by-step explanation:
To start off, you can divide the right side of the equation by x to get rid of most of the x's so you get the polynomial x^4 - 10x^2 + 9. This means that f(x) = x^4 - 10x^2 + 9x. By factoring the right side of the equation, you get f(x) = (x^2 - 1)(x^2 - 9). I think the minimum value is 1 and the maximum value is 3.
<h3>Answer :- </h3>
<h3>Solution :- </h3>
- 2x + 42 = 90
- 2x = 90 - 42
- 2x = 48
- x = 48/2
- x = 24
<em>Hope</em><em> it</em><em> helps</em><em> </em><em>~</em>